1991
DOI: 10.1055/s-2007-1024660
|View full text |Cite
|
Sign up to set email alerts
|

Ratings of Perceived Exertion Among Standard Treadmill Protocols and Steady State Running

Abstract: The purpose of this study was to determine if differences exist in ratings of perceived exertion (RPE) at a predetermined relative heart rate between two standard treadmill protocols and steady state exercise in a field setting. Thirty healthy male (N = 15) and female (N = 15) volunteers were maximally tested using the standard Bruce and a modified Balke (3.0 mph with 2.5% grade each two minutes) protocols. Each subject was randomly assigned to one treadmill protocol first, and then completed the second test f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…The lack of correspondence between RPE and %HRR observed in a substantial proportion (43%) of our sample has also been reported in healthy adults 10, 26-27 and cardiac patients 26, 28-29 . For example, Whaley et al 26 reported that 39% and 32% of healthy subjects and cardiac patients respectively reported an RPE above or below the expected value at 60% HRR.…”
Section: Discussionsupporting
confidence: 64%
“…The lack of correspondence between RPE and %HRR observed in a substantial proportion (43%) of our sample has also been reported in healthy adults 10, 26-27 and cardiac patients 26, 28-29 . For example, Whaley et al 26 reported that 39% and 32% of healthy subjects and cardiac patients respectively reported an RPE above or below the expected value at 60% HRR.…”
Section: Discussionsupporting
confidence: 64%
“…The findings from the present investigation support the results from earlier studies that found higher RPEs at fixed relative intensities (40.60,70 and 80% MHRR) during the Balke protocol compared to the Bruce protocol [11,36] or simulated exercise training I11 1. Based on these previous studies, we had speculated that the higher RPE score during the Balke protocol may have been due to a greater BLC accumulation associated with the longer exercise test time prior to the attainment of the matched physiological value (i.e., H R O~ m2).…”
Section: Resultssupporting
confidence: 91%
“…Similarly, it should be noted that RPE at the same relative intensity has been shown to vary in both children and adults during different exercise tests. Glass et al (1991) reported that the RPE at ~65% of VO 2 max was significantly lower in adult men and women during a standard Bruce treadmill protocol compared to a modified Balke treadmill protocol. In addition, Mahon et al (1992) reported that the RPE at VT in a group of children was significantly lower (1 unit on the Borg 6-20 RPE scale) on the second of two identical treadmill tests performed on separate days although there were no differences in VT.…”
Section: Discussionmentioning
confidence: 96%